G-Frames, Fusion Frames and the Restricted Isometry Property: Mohammad Sadegh Asgari, Golsa Kavian - Team, Support (Thai Journal of Mathematics, 2020)
In this paper we study the restricted isometry property for g-frames, we will show how to use tight g-frames that have the restricted isometry property to construct fusion frames. We also study the conditions which under removing some element from a g-frame, again we obtain another g-frame so that Theorem 4.3 obtained in [M.S. Asgari, On the stability of fusion frames (frames of subspaces), Acta Math. Sci. (Ser. B) 31 (4) (2011) 1633–1642] is a special case of it.